Relacje pacjent-lekarz w psychiatrii aksjologicznej Antoniego Kępińskiego - Aleksandra Bulaczek (Studia Ecologiae et Bioethicae)
The author of the article helps to understand the relation patient-doctor in the light of axiological psychiatry developed by Antoni Kępiński. Kępiński was not a typical doctor who, with great dedication and reverence, fulfilled his duties towards patients. First of all, he paid special attention to the uniqueness and specificity of the level of contact between a doctor and a patient and pointed out its matey character. The article also introduces the sources of axiological psychiatry developed by Kępiński, which should be found in the philosophy of dialogue. In the light of the works of Kraków psychiatrist one can notice that his philosophical anthropology was saturated with the influence of dialogue thought. According to Kępiński, only a specific kind of emotional relationship based on empathy and trust could be the key to complete knowledge of the man fighting with mental illnesses.